Factors Affecting Financial Literacy and Financial Behavior of Working Young Adults in India - Linge, Ashish A.; Kakde, Baldeo B.; Jiwani, Adil (Indian Journal of Finance, 2025)
Purpose : This study aimed to analyze various factors affecting the financial literacy and financial behavior of working young adults in India. Design/Methodology/Approach : A sample survey was conducted among 773 working young adults in India. The participants were selected by using availability, purposive, and snowball sampling techniques. The data was analyzed by applying the SEM technique. Findings : The results revealed that parental socialization, peer influence (PI), and attitude toward money significantly influenced subjective financial literacy. Similarly, PI and attitude toward money also significantly influenced objective financial literacy, but parental socialization did not have a significant impact on it. Practical Implications : The results have significant implications for various stakeholders, viz, regulators, financial institutions, investment advisory, managers, etc., in the financial industry in understanding the various facets of the financial behavior of youth in India. Originality/Value : This study is the first to design and test the interrelationships between the variables in the conceptual framework in the context of working young adults in India.